Solar Tracking System for Self-Propelled Vehicle - Nguyễn Phan Anh Quốc; Nguyễn Văn Hiếu (Journal of Technical Education Science, 2012)
This work will report on the design of solar tracking system in view of the application of solar panels and solar car with tracking solar panel. Tracking solar equipment is an Electro Mechanic System that drives the solar panel toward the sun. It can be reduced to the minimum of angle between the light ray and the normal of solar panel. Consequently, the effect of photo-electric transformation of tracking solar system will be higher than static solar panel. The two axes tracking solar system was operated by the two bipolar step motors with the mechanism of transfer force of screws and begel gears. The electronic devices of IC L297 and L298 were applied to drive the motors. The control signals were done by the micro processor of PIC 18F4550 to process the voltage levels which obtained from light dependent resistors (LDR) and solar cell panels. The measurement data demonstrated the capacity of charge for accumulator from solar tracking panel was better than the normal solar panel. The comparison with other solar tracking systems was done to affirm the feasibility of our studies in this solar tracking work.